How NFTs (Non-Fungible Tokens) Are Perceived in Romania - Ionut TANASE; Bianca Cristiana VOICU; Raluca-Giorgiana (POPA) CHIVU (Communications of International Proceedings, 2022)
Non-fungible tokens (NFTs) have gotten a lot of interest since the starting of 2021. Among the most visible public triumphs of blockchain innovation is the present prominence of non-fungible token (NFT) marketplaces. NFTs are permissions to every cryptocurrency, comprising photographs, movies, entertainment, and sometimes even chunks of imaginary spaces, which can be sold on the blockchain. Non-Fungible Tokens (NFTs) have lately attracted a lot of shareholder interest, with certain NFTs achieving auction values that were previously unimaginable  for a non-fungible digital commodity. NFT markets have wreaked havoc on the digitalized artwork and antiquities industries by decreasing the barriers to entry for artists and designers and allowing them to sell one-of-a-kind versions of their work, similar to how traditional marketplaces do for genuine art and treasures. These assets have also gained a lot of popularity in Romania, when a number of artists, musicians and bands released their own collections, displaying unique art, music and generative images, some showcasing traits from the Romanian folklore.  In this paper we had a quantitative survey on a group of adults of Romania and analyze their perception on NFTs and whether they are willing to invest in such assets
Keywords: nft; nft perception; nft perception in Romania; nft investing; nft technology